Aplicación de una metodología difusa a la negociación de la reforma laboral - Carmen Lozano Gutiérrez; Federico Fuentes Martín (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2013)
– In this paper it is carried out a methodology based on Fuzzy Logic tech- niques for searching a solution which has been reached by consensus. This solution is related to labour reform and considers Trade Unions, Employers' Associations, and Government opinions. The proposed model belongs to the field of a qualitative or structural methodology based on uncertainty. This viewpoint is particularly appropriate at present when economic and social changes are so fast and deep that it is impossible to know what the future will bring.
Keywords: A12; C15; C61; 330; labour reform; crisis; fuzzy logic